Control of Coconut Shell Briquette Making Machine Based on Arduino Microcontroller - silfani, Aulia; Muskhir, Mukhlidi; Sukardi; Sardi, Juli (Department of Electrical Engineering Universitas Negeri Padang, 2024)
The arduino microcontroller processing system as the brain of this system organizes and controls the automation process. The proximity sensor will be used to measure and calculate the distance between the sensor and the object to be cut. The arduino microcontroller will control the servo motor and proximity sensor needed to drive the mechanical part. Automatic briquette printers can be used to save time and increase the amount of production in a short time. After testing the briquette printer automatically and manually, it is known that when using an automatic briquette printer is able to produce 118 briquettes in 480 seconds, while when using a manual briquette printer is only able to produce 43 briquettes with the same time of 480 seconds. From the results of the comparison of automatic and manual briquette printers, it can be compared that the time efficiency of automatic tools is an average production cycle of 96 seconds with the number of briquettes printed 23.6 pieces with a score of 8, while in manual tools the average production cycle is 96 seconds, the average number of briquettes printed is 8.6 pieces and the average quality score is cut 7